Urban rainfall modelling refined: the crucial impact of Digital Terrain Model resolutions in 3D city models - Syed Ahmad Fadhli Syed Abdul Rahman,; Khairul Nizam Abdul Maulud,; Uznir Ujang,; Wan Shafrina Wan Mohd Jaafar,; Lam, Kuok Choy; Sharifah Nurul Ain Syed Mustorpha, (Penerbit Universiti Kebangsaan Malaysia, 2025)
Urbanization and climate change are exerting increasing pressure on urban infrastructures and ecosystems, necessitating advanced rainfall modelling for sustainable city planning and effective water resource management. Accurate urban rainfall modelling is essential for predicting and mitigating flood risks, optimizing drainage systems, and ensuring the resilience of urban environments to climate variability. One critical yet often overlooked component in this modelling process is the resolution of Digital Terrain Models used within 3D city models. The resolution of DTMs significantly influences the precision of rainfall-runoff simulations, which are vital for predicting urban flooding and managing water resources effectively. This study employs a comparative analysis of high-resolution (0.5 meter LiDAR), medium-resolution (5 meter IFSAR), and low-resolution (30 meter SRTM) DTMs to assess their impact on the modelling of rainfall events in Section 13 of Petaling Jaya urban settings. By focusing on Level of Detail 1 building models, which represent the basic geometry of buildings, and open terrain footprints, which are areas without buildings or dense vegetation, this study assesses water level trends in urban environments, identifying areas with increasing (up trends) or decreasing (down trends) water levels. The findings highlight that the high-resolution DTMs provide the most accurate water depth predictions, essential for precise urban flood modelling. Medium-resolution DTMs offer a balance between detail and computational efficiency, while low-resolution DTMs, despite indicating significant trends, show higher variability and less reliability. This study demonstrates that high-resolution DTMs are critical for developing accurate urban rainfall models, which are essential for sustainable urban development and effective flood management.